Pengaruh Gaya Belajar Terhadap Intensitas dan Prestasi Belajar Peserta Didik Di MI Al Hidayah 02 Betak Kecamatan Kalidawir Kabupaten Tulungagung - Rifqi Nuril Janah; Muhamad Zaini (The Elementary Journal, 2024)
This research is motivated by the characteristics of students' learning methods or attitudes, known as learning styles. One of the well-known learning style theories is the "VAK learning style" theory developed by Bobbi de Poter and Mike Henarcki. A learning process that is appropriate to the character of students can influence the intensity and achievement of students' learning well. This research uses a quantitative approach with ex-postfacto correlational research. The population is all students from class I to class VI at MI Al-Hidayah 02 Betak, Kalidawir, Tulungagung. The sampling technique was carried out using a purposive sampling technique by taking samples with a specific purpose. The sample chosen was class IV students at MI Al-Hidayah 02 Betak, Kalidawir, Tulungagung. The data analysis techniques used are hypothesis prerequisite tests (normality and linearity tests) and hypothesis tests (simple linear regression test and MANOVA test). The results of the research show that (1) based on the results of the hypothesis test, it is found that learning style influences students' learning intensity by The resulting value of t = 4.943 and it is known that t table = 2.093 and the significance level is 0.000 < 0.05, meaning that Ho is rejected and Ha is accepted. (2) Based on the results of the hypothesis test, it was found that learning style has an influence on students' learning achievement with the result of a value of t = 2.046 and it is known that t table = 2.093 and a significance level of 0.049 < 0.05, meaning that Ho is rejected and Ha is accepted. (3) Based on the results of the hypothesis test, it was found that learning style influences students' learning intensity and achievement with a significance value for Pillai's Trace of 0.000, Wilk's Lambda of 0.000, Hotelling's Trace of 0.000, Roy's Largest Root of 0.000. So, the significance value is smaller than the 0.05 significance level, meaning that Ho is rejected and Ha is accepted. So it can be concluded that learning style influences the intensity and learning achievement of students at MI Al Hidayah 02 Betak, Kalidawir District, Tulungagung Regency.